Severe Postpartum Hemorrhage Complicated with Liver Infarction Resulting in Hepatic Failure Necessitating Liver Transplantation. (11th June 2018) - Peng, I-Ting; Chung, Ming-Ting; Lin, Ching-Chung
Abstract : Postpartum hemorrhage remains a major threat to maternal health. Intervention after critical blood loss or development of disseminated intravascular coagulation may lead to disastrous organ failure and poor outcomes. A 30-year-old woman was transferred to our emergency department due to massive postpartum hemorrhage. Shock and disseminated intravascular coagulation ensued, and the patient's condition quickly deteriorated. We performed an emergency hysterectomy, but blood loss had been massive. Moreover, there was another episode of internal bleeding that led to further blood loss. Ischemic injury to the liver was tremendous, with resulting progressive jaundice and hepatic encephalopathy. The patient required liver transplantation. Imaging studies and operative findings showed a large area of hepatic infarction. Unfortunately, the patient died of intractable sepsis shortly after liver transplantation. Disseminated intravascular coagulation and resultant hepatic infarction combined with ischemic hepatitis were the direct cause of death in our case.